2014
DOI: 10.1016/j.entcom.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Flow framework for analyzing the quality of educational games

Abstract: The challenge of educational game design is to develop solutions that appeal to as many players as possible, but are still educationally effective. One foundation for analyzing and designing educational engagement is the flow theory. This article presents a flow framework that describes the dimensions of flow experience that can be used to analyze the quality of educational games. The framework also provides design-support for producing good educational games, because it can be used to reveal ways to optimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 52 publications
(67 reference statements)
1
76
0
8
Order By: Relevance
“…According to Csikszentmihalyi (1990), this concept can be defined as a complete state of cognitive absorption or engagement in a task, in which the individual is not affected by thoughts or emotions unrelated to the task. Kiili et al, (2014) extended the flow theory to include playability and demonstrated the potential of the flow theory in evaluating the quality of educational games.…”
Section: Motivation Theories In Dgblmentioning
confidence: 99%
“…According to Csikszentmihalyi (1990), this concept can be defined as a complete state of cognitive absorption or engagement in a task, in which the individual is not affected by thoughts or emotions unrelated to the task. Kiili et al, (2014) extended the flow theory to include playability and demonstrated the potential of the flow theory in evaluating the quality of educational games.…”
Section: Motivation Theories In Dgblmentioning
confidence: 99%
“…That is, an extremely competitive game may create a potential barrier for students to enjoy or engage in gameplay. As the subjective playing experience is a crucial part of the game achievements (Kiili et al 2014), teachers may guide students to be more self-efficient in learning Chinese idioms before asking them to participate in a one-on-one competition to enhance their interest to play.…”
Section: Implicationmentioning
confidence: 99%
“…Este conjunto foi baseado em um trabalho anterior dos mesmos autores, também voltado à avaliação de jogabilidade, chamado HEP (Heuristics to Evaluate Playability), voltados ao gameplay, usabilidade, mecânica e enredo (DESURVIRE e WIBERG, 2008). Ainda em relação à ferramentas voltadas à avaliação de jogos por especialistas, Kiili et al (2014) elaboraram um framework onde se pode avaliar a capacidade de um jogo educacional incentivar a experiência de fluxo. Considera-se que este tipo de ferramentas é muito útil durante a etapa de projeto (ou design) de jogos, já que, por terem uma natureza qualitativa, permitem que sejam explorados diferentes soluções para os problemas detectados.…”
Section: Avaliação De Usabilidade E Da Experiência Do Usuário Em Jogunclassified